We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
194
1
avatar+4116 

#18,19 Help.

 Feb 12, 2018
 #1
avatar+101228 
+1

√ [ 250x^16 ]  / √ [2x ]  =

 

√  [  ( 250x^16) / ( 2x) ]  =

 

√ [ 125 x^15 ]  =

 

√25*√5 * √x^14 * √ x   =

 

5 * √5  * x^7 * √x   =

 

5x^7 √ [  5x ]

 

 

The second is just like  having  3x  -  6x  =  - 3x

 

So we have

 

33√[2a ]  - 63√ [2a ]  =   -33√[2a ]

 

 

 

cool cool cool

 Feb 12, 2018

12 Online Users

avatar
avatar